Fungos gasteroides (Basidiomycota, Agaricomycetes) de três áreas de semiárido no Estado do Ceará, Brasil - Rodrigues, Ana Clarissa Moura (2014)
Gasteroid fungi include several distinct lineages of basidiomycetes that were grouped by presenting some striking features in common like angiocarpic development and passive release of basidiospores. For a long period these fungi were accomodate in Gasteromycetes class. However, biochemistry and molecular studies showed the polyphyly of this group and curriently this class lies devoid of taxonomic value. These organisms influence the ecology of the various biomes, however, are poorly studied and knowledge of their diversity in neotropical ecosystems remains insufficient, despite studies that have been developed in recent years. The Brazilian semiarid region has many areas with an unexplored mycobiota. Ceará State has many areas of extreme biological importance and for this study three protected areas were chosen: Área de Proteção Ambiental da Serra da Ibiapaba, Parque Nacional de Ubajara and Área de Proteção Ambiental de Baturité. Therefore, the aim of this study was to inventory gasteroid fungi ocorring in these three areas in the semiarid region of Ceará. The expeditions, herborization and analysis of specimes were based in traditional methodology used to identify gasteroid fungi. Were identified 16 species belong to 5 families: Agaricaceae, Clathraceae, Geastraceae, Nidulariceae and Phallaceae. Morganella nuda Alfredo & Baseia is recorded for the second time in the world, Blumenavia angolensis (Welw. & Curr) Dring and Mutinus elegans (Mont.) E. Fisch. corresponds to a first record in the Brazilian Northeastern. Except for Abrachium floriforme (Baseia & Calonge) Baseia & T.S. Cabral and Geastrum lloydianum Rick, all remaining species are new records for Ceará, increasing the list of gasteroid fungi in the region of 3 for 17 species. Identified species were deposited in the collection of the Herbarium of Universidade Federal do Rio Grande do Norte. Although these areas have proved conducive to the study of gasteroid fungi, more efforts are still needed to increase knowledge of these fungi in the region